Distribuição espacial e temporal da comunidade fitoplanctônica em uma área de malacocultura no município de Anchieta - ES - Schaeffer, Lislane Rocha (2007)
The actual paper was made in the coastol region near Anchieta estuarian area in Espírito Santo State in na malacoculture area. The samples were taken monthly from January to December 2004 in 10 (ten) points: Rio, 1A, 1B, 1C, 2A, 2B, 2C, 3A, 3B, 3C. The analysis made were both a phytoplankton comunity quali-quantitative and environmental variables as water temperature, transparency, pH, salinity, and oxigen dissolved analysis . The water temperature and pH results had little variation throughout the year. The amount of rain changed the water transparency, therefore, pluviosity was the most influencing factor in the local phytoplankton comunity. Diatom were the most significant kind ( concearning a qualitative and quantitative analysis). Density data was low compared to other beach regions, though it showed a high diversity and equitability levels, which assures the well preserved with low environment impact area. The low density and biovolume levels indicate that mussels almost do not depend on phitoplancton comunity to eat. The Bacillariophyceae kind had the most representation concearning toxic species, due to it highest numbers through the year. Phytoplankton species that are potentialy toxic still do not appear, however they should be considered dangerous, since the Anchieta city population sewing system go straight either to Beneventes River or to the sea. This research is an under project of sustain musssel culture from RECOS Milenium Project, sponsored by CNPq since 2004